Comparative life history patterns of female gorillas - Robbins, Martha M.; Akantorana, Moses; Arinaitwe, Joseph; Breuer, Thomas; Manguette, Marie L.; McFarlin, Shannon; Meder, Angela; Parnell, Richard J.; Richardson, Jack L.; Stephan, Claudia; Stokes, Emma J.; Stoinski, Tara S.; et al. (American Journal of Biological Anthropology, 2023)
Objectives Several theories have been proposed to explain the impact of ecological conditions on differences in life history variables within and between species. Here we compare female life history parameters of one western lowland gorilla population (Gorilla gorilla gorilla) and two mountain gorilla populations (Gorilla beringei beringei). Materials and Methods We compared the age of natal dispersal, age of first birth, interbirth interval, and birth rates using long-term demographic datasets from Mbeli Bai (western gorillas), Bwindi Impenetrable National Park and the Virunga Massif (mountain gorillas). Results The Mbeli western gorillas had the latest age at first birth, longest interbirth interval, and slowest surviving birth rate compared to the Virunga mountain gorillas. Bwindi mountain gorillas were intermediate in their life history patterns. Discussion These patterns are consistent with differences in feeding ecology across sites. However, it is not possible to determine the evolutionary mechanisms responsible for these differences, whether a consequence of genetic adaptation to fluctuating food supplies (“ecological risk aversion hypothesis”) or phenotypic plasticity in response to the abundance of food (“energy balance hypothesis”). Our results do not seem consistent with the extrinsic mortality risks at each site, but current conditions for mountain gorillas are unlikely to match their evolutionary history. Not all traits fell along the expected fast-slow continuum, which illustrates that they can vary independently from each other (“modularity model”). Thus, the life history traits of each gorilla population may reflect a complex interplay of multiple ecological influences that are operating through both genetic adaptations and phenotypic plasticit